Currency Crisis and Contagion : Evidence From Exchange Rates and Sectoral Stock Indices of the Philippines and Thailand - Nagayasu, Jun. (Washington, D.C. : International Monetary Fund, 2000)
This paper analyzes empirically the recent Asian financial crisis using high frequency data of exchange rates and stock indices of the Philippines and Thailand. Utilizing standard time-series techniques, this study confirms that there is evidence that developments in some sectoral indices-including those of banking and financial sectors-seem to have caused upward pressure on exchange rates. A correlation between some of these variables is also found to be strong across countries in the crisis period, thereby confirming the importance of the linkages between financial markets as a transmission channel of the Thai crisis to the Philippines.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet